2006
DOI: 10.1037/0012-1649.41.6.189
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and individual differences in pure numerical estimation.

Abstract: The authors examined developmental and individual differences in pure numerical estimation, the type of estimation that depends solely on knowledge of numbers. Children between kindergarten and 4th grade were asked to solve 4 types of numerical estimation problems: computational, numerosity, measurement, and number line. In Experiment 1, kindergartners and 1st, 2nd, and 3rd graders were presented problems involving the numbers 0-100; in Experiment 2, 2nd and 4th graders were presented problems involving the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
763
10
39

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 615 publications
(892 citation statements)
references
References 17 publications
67
763
10
39
Order By: Relevance
“…(It should be noted that the linearity and slope indexes from our young preschoolers were somewhat lower than those reported by Muldoon et al, 2011, on their sample of Chinese preschoolers, which can be explained by the fact that their sample was older [M age = 4.5 years] than our young preschoolers.) Similarly, for the 0-100 number line, we found that the linearity indexes seemed much higher than those reported by Siegler and his colleagues for American kindergarteners (see Table 7) and, in fact, were similar to those for first and second graders in Siegler's American samples (Booth & Siegler, 2006;Laski & Siegler, 2007;Siegler & Booth, 2004;Siegler & Mu, 2008). Finally, for the 0-1000 number line, the linearity indexes were higher than those obtained for American second graders (Booth & Siegler, 2006;Opfer & Siegler, 2007;Siegler & Opfer, 2003).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…(It should be noted that the linearity and slope indexes from our young preschoolers were somewhat lower than those reported by Muldoon et al, 2011, on their sample of Chinese preschoolers, which can be explained by the fact that their sample was older [M age = 4.5 years] than our young preschoolers.) Similarly, for the 0-100 number line, we found that the linearity indexes seemed much higher than those reported by Siegler and his colleagues for American kindergarteners (see Table 7) and, in fact, were similar to those for first and second graders in Siegler's American samples (Booth & Siegler, 2006;Laski & Siegler, 2007;Siegler & Booth, 2004;Siegler & Mu, 2008). Finally, for the 0-1000 number line, the linearity indexes were higher than those obtained for American second graders (Booth & Siegler, 2006;Opfer & Siegler, 2007;Siegler & Opfer, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…This hypothesis appeared to be supported. When comparing our results with those from previous studies of Western children, it appears that the estimates of Chinese preschoolers were more accurate and linear on the 0-10, 0-100, and 0-1000 number lines than their Western age mates (Booth & Siegler, 2006;Muldoon et al, 2011;Siegler & Booth, 2004;Siegler & Mu, 2008;. Table 7 shows a summary of previous studies based on Western samples.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations